Heat Transfer Analysis of Buffer and Combustion Chamber of Waste Combustion Device Fueled by Used Oil and Water - Setyo HARIYADI SURANTO PUTRO Hariyadi (Journal of Research in Social Science and Humanities, 2025)
Departing from the lack of utilization of used oil waste and the absence of a good tool to utilize used oil in addition to processing waste waste quickly and thoroughly. On the other hand, when used as fuel, used oil does not produce perfect combustion so it is necessary to accom-pany the waste fuel tool with water so that the flame is stronger. The methods used in this de-sign include making tools, collecting data, making models in software, then analyzing struc-tures using the Finite Element Analysis (FEA) simulation method. The application used is Solidwork. Numerical simulation can show heat transfer by convection and conduction. The heat source from the bottom of the burner can be shown to creep from the bottom to the top of the burner. The heat transfer tends to be uneven from one part to another as shown in the heat transfer graph.